2008
DOI: 10.1038/nature07421
|View full text |Cite
|
Sign up to set email alerts
|

Conformational transition of Sec machinery inferred from bacterial SecYE structures

Abstract: Over 30% of proteins are secreted across or integrated into membranes. Their newly synthesized forms contain either cleavable signal sequences or non-cleavable membrane anchor sequences, which direct them to the evolutionarily conserved Sec translocon (SecYEG in prokaryotes and Sec61, comprising α-, γ-and β-subunits, in eukaryotes). The translocon then functions as a proteinconducting channel 1 . These processes of protein localization occur either at or after translation. In bacteria, the SecA ATPase 2,3 driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
170
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(177 citation statements)
references
References 41 publications
(45 reference statements)
6
170
0
1
Order By: Relevance
“…This structure supports the idea that membrane segments can be inserted before the plug has vacated its central position (15). The crystal structure of the Thermus thermophilus SecYE with a bound anti-SecY Fab fragment shows only a partial opening of the lateral gate at the cytoplasmic side, also termed the hydrophobic crack (16). Also here, the plug domain remains at its central position.…”
supporting
confidence: 77%
“…This structure supports the idea that membrane segments can be inserted before the plug has vacated its central position (15). The crystal structure of the Thermus thermophilus SecYE with a bound anti-SecY Fab fragment shows only a partial opening of the lateral gate at the cytoplasmic side, also termed the hydrophobic crack (16). Also here, the plug domain remains at its central position.…”
supporting
confidence: 77%
“…the LPS deacylase LpxR from Salmonella typhimurium (PDB file 3FID) (Rutten et al, 2009), and of a typical a-helical inner-membrane protein, i.e. the SecYE translocon of Thermus thermophilus (PDB file 2ZQP) (Tsukazaki et al, 2008), are shown on the left and the right, respectively.…”
Section: Transport Of Omps Across the Bacterial Inner Membranementioning
confidence: 99%
“…In bacteria, the SecYEG membrane protein complex provides pathways of protein translocation across and integration into the cytoplasmic membrane (1)(2)(3). The crystal structures of SecYEG reveal an hourglass-shaped pore across the membrane, which is plugged with a short helix in the resting state (4)(5)(6). As a substrate comes in, either by SecA-mediated translocation or signal recognition particle (SRP)-mediated cotranslational targeting, the plug is displaced, and the channel with the open gate accepts the translocating chain (7)(8)(9).…”
mentioning
confidence: 99%
“…SecA translocates not only secretory proteins but also large extracytoplasmic regions of integral membrane proteins (10). For lipid phase integration, a transmembrane region of the substrate exits the pore laterally through the lateral gate that opens toward the lipid phase of the bilayer (4)(5)(6). This process is thought to be driven by the thermodynamic partition of the hydrophobic segment to the lipidic environment (11).…”
mentioning
confidence: 99%